2020
DOI: 10.3389/fpsyg.2020.574393
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism and Fear of COVID-19. The Interplay Between Boredom, Fantasy Engagement, and Perceived Control Over Time

Abstract: The Italian government adopted measures to prevent the spread of coronavirus 2019 (COVID-19) infection from March 9, 2020, to May 4, 2020 and imposed a phase of social distancing and self-isolation to all adult citizens. Although justified and necessary, psychologists question the impact of this process of COVID-19 isolation on the mental health of the population. Hence, this paper investigated the relationship between neuroticism, boredom, fantasy engagement, perceived control over time, and the fear of COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 57 publications
(64 reference statements)
16
51
1
Order By: Relevance
“…• Five cross-sectional analytic studies (Iasevoli et al, 2020;Hao et al, 2020;Caci et al, 2020;Balsamo and Carlucci, 2020;Ye et al, 2020), • Two case reports (Smith et al, 2020;Fischer et al, 2020), • Two case series (Ferrando et al, 2020;Valdés-Florido et al, 2020) , • Two retrospective studies (Liu et al, 2020;Parra et al, 2020), • A service evaluation (Rohde et al, 2020),…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…• Five cross-sectional analytic studies (Iasevoli et al, 2020;Hao et al, 2020;Caci et al, 2020;Balsamo and Carlucci, 2020;Ye et al, 2020), • Two case reports (Smith et al, 2020;Fischer et al, 2020), • Two case series (Ferrando et al, 2020;Valdés-Florido et al, 2020) , • Two retrospective studies (Liu et al, 2020;Parra et al, 2020), • A service evaluation (Rohde et al, 2020),…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…One study (Liu et al, 2020) recruited hospitalized patients with schizophrenia with or without suspected COVID-19 in Hubei Province (China), five studies (Parra et al, 2020;Ferrando et al, 2020;Smith et al, 2020;Varatharaj et al, 2020;Sharma et al, 2020) recruited people with and without psychiatric illness who were confirmed with COVID-19. Furthermore, nine studies (Rohde et al, 2020;Iasevoli et al, 2020;Hao et al, 2020;Valdés-Florido et al, 2020;Fischer et al, 2020;Marton et al, 2020;Caci et al, 2020;Balsamo and Carlucci, 2020;Ye et al, 2020) included people with and without psychiatric illness who did not have any SARS-COV-2 infection. One study (Ye et al, 2020) observed medical and non-medical students.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations